The prevalence and influence of psychosocial factors on technical refinement amongst highly-skilled tennis players - Toner, J.; Carson, H. J.; Collins, D.; Nicholls, A. (International Journal of Sport and Exercise Psychology, 2020)
The present study investigated the prevalence and influence of psychosocial factors amongst a sample of highly-skilled athletes who had previously attempted to refine their technique. Semi-structured qualitative interviews were conducted with eight tennis players to gain an in-depth understanding of their experiences during the process. Results revealed that participants sought to refine their technique in order to address an "attenuated" movement pattern perceived as causing a competitive disadvantage. Addressing the psychosocial factors of interest here, commitment and confidence were reportedly important concomitants during the refinement process. Upon reflection, participants indicated that taking a break from competition and dedicating more time to the refinement might have increased the likelihood of effective change and performance improvement. Overall, findings indicate that psychosocial factors have a significant influence on players` ability to successfully enact technical refinement. However, it is suggested that greater consideration towards other motoric factors could also have improved levels of success. In conclusion, while the importance for change was understood, there is a need for improved understanding and planning in terms of how a coach might operationalise these factors within training for the competition environment.